Design of Educational Facility Service Standards in Indonesia (Case: Junior High School in Lampung Province) - Sri Utami, Rahma Kurnia; Sudarmi, Sudarmi; Afriansyah, Rafif; Akbar, M Satria (Jurnal Penelitian Geografi (JPG), 2024)
The educational facility standards in Indonesia do not meet regional needs. A strategic design aligned with regional demographics is necessary. This research aims to create verified standardized designs for educational facility services. The research uses quantitative methods with formal schools at junior high school level in Lampung Province as the research object. The research uses documentation data with secondary data analysis techniques and descriptive statistics. The research results denote (1) educational services condition facilitated by the government in Lampung Province for junior high school level according to Ministry of Education criteria is 16.20%, while according to BSN criteria is 38.87%. The amount of junior high school level standard, both according to Permendiknas and BSN criteria, is stated undersupply. (2) The standard design used is Utami version (2023), modified according to Ministry of Education and BSN criteria, using threshold changes and number of school-age population. The design is equipped with school type criteria: type A, B, and C. (3) Implementation results indicate that if the government maximizes the junior high school facilities with type A relatively then it can be declared as capable of meeting the standard needs for the number of schools, even without the involvement of private schools. Keyword: Educational facility; Service standards; Design; Junior high school; Lampung province